International economics : theory and policy - Krugman, Paul R.; Obstfeld, Maurice (Boston : Pearson Addison-Wesley, 2009)
International Economics: Theory and Policy is a proven approach in which each half of the book leads with an intuitive introduction to theory and follows with self-contained chapters to cover key policy applications. The Eighth Edition integrates the latest research, data, and policy in hot topics such as outsourcing, economic geography, trade and environment, financial derivatives, the subprime crisis, and China's exchange rate policies.
Chapter 1. Introduction -- Chapter 2. World Trade: An Overview -- Chapter 3. Labor Productivity and Comparative Advantage: The Ricardian Model -- Chapter 4. Resources, Comparative Advantage, and Income Distribution -- Chapter 5. The Standard Trade Model -- Chapter 6. Economies of Scale, Imperfect Competition, and International Trade -- Chapter 7. International Factor Movements -- Chapter 8. The Instruments of Trade Policy -- Chapter 9. The Political Economy of Trade Policy -- Chapter 10. Trade Policy in Developing Countries -- Chapter 11. Controversies in Trade Policy -- Chapter 12. National Income Accounting and the Balance of Payments -- Chapter 13. Exchange Rates and the Foreign Exchange Market: An Asset Approach -- Chapter 14. Money, Interest Rates, and Exchange Rates -- Chapter 15. Price Levels and the Exchange Rate in the Long Run -- Chapter 16. Output and the Exchange Rate in the Short Run -- Chapter 17. Fixed Exchange Rates and Foreign Exchange Intervention -- Chapter 18. The International Monetary System, 1870-1973 -- Chapter 19. Macroeconomic Policy and Coordination Under Floating Exchange Rates -- Chapter 20. Optimum Currency Areas and the European Experience -- Chapter 21. The Global Capital Market: Performance and Policy Problems -- Chapter 22. Developing Countries: Growth, Crisis, and Reform Mathematical Postscripts.
Includes bibliographical references and index.
1
Keywords: EMBA; International economic relations; International finance